Benchmarking and library quality maturity - Wilson, Frankie; Town, J. Stephen (Emerald, 2005)
It remains unresolved from the literature whether benchmarking is a useful and appropriate tool for the library and information services sector. The aim of this research was to gather evidence to establish whether benchmarking provides a real and lasting benefit to library and information services. The study investigated the long term effects of a benchmarking exercise on the quality level of three UK academic libraries. However, an appropriate framework for assessing the quality level of libraries is not present in the literature, and it was therefore necessary for such a framework to be developed. This article describes and provides initial characterisation of the framework developed - the Quality Maturity Model. The evidence from the investigation showed that the two libraries which were at stage one on the QMM before the benchmarking exercise remained there; and the library which scored at the penultimate level, level four, before benchmarking, was, four years afterwards, at level five. The tentative conclusion drawn were that benchmarking may only be appropriate for organisations with a existing high level of quality maturity. Much further work is proposed.
Keywords: Benchmarking; Quality; Library Services